Structure and Function of Intra–Annual Density Fluctuations: Mind the Gaps - Battipaglia, Giovanna; Campelo, Filipe; Vieira, Joana; Grabner, Michael; De Micco, Veronica; Nabais, Cristina; Cherubini, Paolo; Carrer, Marco; Bräuning, Achim; Čufar, Katarina; Di Filippo, Alfredo; García-González, Ignacio; et al. (Frontiers in Plant Science, 2016)
Tree rings are natural archives of climate and environmental information with a yearly resolution. Indeed, wood anatomical, chemical, and other properties of tree rings are a synthesis of several intrinsic and external factors, and their interaction during tree growth. In particular, Intra-Annual Density Fluctuations (IADFs) can be considered as tree-ring anomalies that can be used to better understand tree growth and to reconstruct past climate conditions with intra-annual resolution. However, the ecophysiological processes behind IADF formation, as well as their functional impact, remain unclear. Are IADFs resulting from a prompt adjustment to fluctuations in environmental conditions to avoid stressful conditions and/or to take advantage from favorable conditions? In this paper we discuss: (1) the influence of climatic factors on the formation of IADFs; (2) the occurrence of IADFs in different species and environments; (3) the potential of new approaches to study IADFs and identify their triggering factors. Our final aim is to underscore the advantages offered by network analyses of data and the importance of high-resolution measurements to gain insight into IADFs formation processes and their relations with climatic conditions, including extreme weather events.